Long term clinical outcome of chronic hepatitis C patients with sustained virological response to interferon monotherapy. Issue 10 (10th September 2004) - Veldt, B J; Saracco, G; Boyer, N; Cammà, C; Bellobuono, A; Hopf, U; Castillo, I; Weiland, O; Nevens, F; Hansen, B E; Schalm, S W
Abstract : Background: The key end point for treatment efficacy in chronic hepatitis C is absence of detectable virus at six months after treatment. However, the incidence of clinical events during long term follow up of patients with sustained virological response is still poorly documented and may differ between the Eastern and Western world. Aims: To assess clinical end points during long term follow up of European patients with a sustained virological response to interferon monotherapy. Methods: Meta-analysis of individual patient data from eight European protocolled follow up studies of interferon treatment for chronic hepatitis C. Results: A total of 286 sustained virological responders and 50 biochemical responders (detectable virus but normal alanine aminotransferase levels) were followed up for 59 months. Fifteen sustained virological responders (5.2%) had cirrhosis before treatment and 112 (39%) had genotype 1. The late virological relapse rate after five years of follow up was 4.7% (95% confidence interval (CI) 2.0–7.4) among sustained virological responders; all late relapses occurred within four years after treatment. Among sustained virological responders, the rate of decompensation after five years of follow up was 1.0% (95% CI 0.0–2.3) and none developed hepatocellular carcinoma (HCC). Survival was comparable with the general population, matched for age and sex, the standard mortality ratio being 1.4 (95% CI 0.3–2.5). Clinical outcome of patients with cirrhosis was similar to other sustained virological responders. For biochemical responders, the rates of development of decompensation and HCC during long term follow up were 9.1% (95% CI 0.5–17.7) and 7.1% (95% CI 0–15.0), respectively. Conclusions: Five year survival of European sustained virological responders was similar to the overall population, matched for age and sex. No HCCs were detected during long term follow up.